Factors associated to the adherence to antiretroviral treatment in HIV-infected adults: cross-sectional study - Samuel Spiegelberg Zuge; Marcelo Ribeiro Primeira; Eduardo Remor; Tânia Solange Bosi de Souza Magnago; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin (Universidade Federal de Santa Maria, 2017)
Aim: to analyze factors associated to the adherence to antiretroviral treatment in adults with HIV. Method: a cross-sectional study with 179 adults attending a specialized service in the South of Brazil. To assess adherence, the "Questionnaire for the Evaluation of Adhesion to Antiretroviral Treatment" (CEAT-VIH) was used. The results were evaluated with descriptive and inferential statistics (Poisson regression). Results: Among the participants, 83.2% were defined as non-adherent to antiretroviral therapy. Lower level of schooling, difficulty in maintaining health service attendance, propensity for alcoholism, change in lifestyle and use of psychiatric medications were associated with noncompliance. Conclusions: the early diagnosis of adherence allows the planning of educational actions focused on the characteristics associated with non-adherence.